The effect of integrating Kahoot! and peer instruction in the Spanish flipped classroom : the student perspective - González Ruiz, Cristina (2021)
In recent years, the use of Student Response System (SRS) technology in higher education settings has gained popularity as research demonstrates its effectiveness in achieving desired outcomes, especially when paired with peer interaction. This article explores students’ perceptions of integrating the Game-based Student Response System (GSRS) Kahoot! in two Spanish flipped classrooms, supported by the Peer Instruction (PI) technique, at a university in Singapore. Adopting an action research approach, quantitative and qualitative data from 32 undergraduates were gathered through a questionnaire. The findings revealed that students perceived the use of Kahoot! to be beneficial in terms of: (1) increasing engagement and motivation to learn; (2) improving the understanding of concepts; and (3) contributing to a positive learning environment. Moreover, students found that PI, in particular, contributed to deepening their grammatical and pragmatic knowledge of Spanish. Implications that may be useful to language teachers are also presented.